Salivary microbiome shifts in caries-free and caries-affected preschool children after educational video intervention and taxonomic profiling of potential biomarkers and their functional profiles - Muhammad Zaki, Ramli (2024)
Dental caries, a widespread phenomenon with global implications, significantly affects young children in preschool settings, including intricate interactions between microbial agents and host-related variables. Despite continuous research efforts, the precise roles of various bacterial species in the development of dental caries and the functional mechanisms that underlie their existence are still not well understood. This lack of clarity has resulted in conflicting findings reported in the existing literature. Moreover, the existing body of research demonstrates a lack of sufficient utilisation of microbial biomarkers and their functional characteristics in evaluating the efficacy of therapies. To bridge this existing knowledge gap, the primary objective of this research endeavour was to comprehensively analyse and describe the taxonomic and functional profiles of salivary microbiomes in young children attending preschool. Additionally, the study sought to identify potential biomarkers that could serve as indicators for the onset and progression of dental caries, as well as evaluate their utility in monitoring the effectiveness of the educational video intervention conducted. This study involved the collection of saliva samples from initially 55 preschool children, and then five caries-free and five caries-affected subjects were involved in the intervention. The children were between the ages of four and six. The saliva samples were collected both before and after a three-month intervention, which consisted of the children watching educational videos focused on oral health and diseases. The intervention was selected based on its capacity to modify everyday oral hygiene practices, thus impacting the composition of the salivary microbiome. Our hypothesis posited those alterations in the microbial composition and functionality may serve as indicators of the effectiveness of the intervention. The samples were subjected to sequencing of the V3 region of the 16S rRNA gene as well as the V4-V5 region, followed by taxonomic profiling using MicrobiomeAnalyst. Two potential biomarkers were found, and predictions were made regarding their functional characteristics using PICRUSt2. The results of our study indicated changes in the microbial composition in both caries-free and caries-affected groups after the intervention. However, these changes were not sufficient to definitively establish the effectiveness of the intervention. Nevertheless, it was shown that two bacterial species, Fusobacterium periodonticum in the caries-free group and Prevotella melaninogenica in the caries-affected group, exhibited potential as biomarkers. Both species exhibited statistically significant changes in their enzyme expressions following the intervention, suggesting the potential effectiveness or ineffectiveness of the intervention. The decreased level of 1-deoxy-D-xylulose-5-phosphate synthase expressed by F. periodonticum was predicted to be a precursor of caries in the initially caries-free group, thus suggested that the intervention was not effective on the group. On the other hand, the significantly reduced expression of phosphoenolpyruvate carboxykinase (ATP) expressed by P. melaninogenica that is important in acid production of the bacteria suggested the effectiveness of intervention on the caries-affected group. These findings provide a basis for future study to explore the functions of these biomarkers and their associated enzymes in the field of caries research. Furthermore, this study underscores the significance of assessing the effectiveness of interventions, such as the educational videos employed in this context, considering the substantial ramifications that untreated caries can entail. By enhancing our comprehension and prognostication of caries incidence and advancement, we can strive towards more efficacious preventive and therapeutic interventions for this widespread ailment.